THE ROLE OF ORGANIZATIONAL TRUST IN ENHANCING JOB ENGAGEMENT - Ali Imad Hamoud; Ahmed Salah Jassam; Abdulaziz Kilan Hatem (Scholars Digest Publishing, 2025)
The research aims to explore the nature of the relationship between organizational trust and job engagement, and to demonstrate the extent to which the independent variable (organizational trust) influences the dependent variable (job engagement). The problem lies in the lack of adequate understanding of the implications of the two research variables and the neglect of the role of the independent variable in enhancing the dependent variable. The research derives its importance from the relevance of its topics in administrative thought, as well as the importance of the organization under study as an academic organization that plays an active role in the development and progress of society. A sample of 78 respondents was selected, and the questionnaire was the primary tool for collecting data and information. A number of appropriate statistical methods were used, using the SPSS statistical program. A number of conclusions and recommendations were reached. The most prominent conclusion was the absence of a motivational system that supports employees who demonstrate job engagement in their work within the organization. The most prominent recommendations included promoting an effective organizational culture that emphasizes the importance of organizational trust and job engagement across all administrative levels.
Keywords: Organizational trust, job engagement.